2016
DOI: 10.17533/udea.vitae.v23n3a04
|View full text |Cite
|
Sign up to set email alerts
|

Efecto Del Tiempo De Almacenamiento Sobre Propiedades Fisicoquímicas Y Antioxidantes De Productos Derivados Del Fruto Agraz (Vaccinium Meridionale Swartz)

Abstract: RESUMENAntecedentes: Agraz es una baya globosa, de color púrpura intenso cuando está madura. Posee alta capacidad antioxidante comparada con bayas del mismo género, atribuido al contenido de compuestos polifenólicos. Objetivo: Evaluar la composición, actividad antioxidante y algunos parámetros microbioló-gicos de pulpa de agraz congelada (PAC) y pulpa de agraz liofilizada (PAL) y analizar su comportamiento durante 60 días de almacenamiento. Métodos: Se midieron pH, °Brix, acidez titulable, % humedad, cenizas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 24 publications
1
4
0
2
Order By: Relevance
“…According to previous reports, Andean blueberry fruits at maturity stages have a soluble solids content ranging between 12 and 18 °Brix, a pH between 2.5 and 3.0, a dry solid content between 17% and 23%, total monomeric anthocyanins between ~329 ± 28 mg cyd-3-glu/100 g, and phenolic compounds ~758.6 ± 62.3 mg gallic acid equivalent/100 g [3,18]. Franco et al found similar values to those reported in this study (Table 1) when they evaluated the physicochemical properties of Andean blueberry nectar [19]. Casati et al [20] evaluated the physicochemical characteristics from berries juices cultivated in Argentina (blueberry, elderberry, blackcurrant, and maqui berry), finding soluble solids contents ranging between 9.0 and 14.8 °Brix, a pH between 3.4 and 4.2, a water activity between 0.983 and 0.989, total polyphenol contents between 2970 and 9340, and total monomeric anthocyanins contents between 288 and 1795.4 mg cyd-3-glu/L.…”
Section: Physicochemical and Morphological Properties Of The Juice Frsupporting
confidence: 85%
“…According to previous reports, Andean blueberry fruits at maturity stages have a soluble solids content ranging between 12 and 18 °Brix, a pH between 2.5 and 3.0, a dry solid content between 17% and 23%, total monomeric anthocyanins between ~329 ± 28 mg cyd-3-glu/100 g, and phenolic compounds ~758.6 ± 62.3 mg gallic acid equivalent/100 g [3,18]. Franco et al found similar values to those reported in this study (Table 1) when they evaluated the physicochemical properties of Andean blueberry nectar [19]. Casati et al [20] evaluated the physicochemical characteristics from berries juices cultivated in Argentina (blueberry, elderberry, blackcurrant, and maqui berry), finding soluble solids contents ranging between 9.0 and 14.8 °Brix, a pH between 3.4 and 4.2, a water activity between 0.983 and 0.989, total polyphenol contents between 2970 and 9340, and total monomeric anthocyanins contents between 288 and 1795.4 mg cyd-3-glu/L.…”
Section: Physicochemical and Morphological Properties Of The Juice Frsupporting
confidence: 85%
“…The Andean Berry Juice (ABJ) was prepared as previously described . Briefly, the lyophilized Andean berry powder was dissolved in a water/sucrose solution (9%, w/v) to obtain a juice of 11.1 °Brix with an acidity of 4.33 mg of citric acid per milliliter (pH 3.06).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…These juices contain most variety of the berry phytochemicals which allows to do an evaluation of their anticarcinogenic capacities (Franco et al, 2016). Although we have previously reported the free radical scavenging capacity of Vaccinium meridionale Sw freeze-dried aqueous extract by chemical methods and the antiproliferative effects against colon cancer cell lines (Maldonado et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Andean Berry Juice (ABJ) was prepared as described previously by Franco-Tobón et al (2016). In brief, freeze-dried powder of Andean Berry was dissolved in sterile water and sucrose to obtain a juice of 11.1° Brix, acidity 4.33 mg citric acid/ml, pH 3.06.…”
Section: Preparation Of Andean Berry Juicementioning
confidence: 99%